Research on measurement of service-oriented development level of manufacturing industry in Henan Province, China (International Journal of Management and Sustainability, 2025)
This study examines the service-oriented development level of Henan Province's manufacturing sector to understand regional servitization patterns and inform industrial transformation policies in central China. The research employs a mixed-methods approach combining cross-sectional and longitudinal analyses. Input-output analysis using 2017 regional data from China's 31 provincial-level regions measures servitization through direct and complete consumption coefficients. A ten-year longitudinal study (2011-2020) analyzes 62 listed manufacturing enterprises using service revenue ratios as proxy indicators for temporal development patterns. Henan's manufacturing servitization level (0.39) surpasses the national average (0.29), ranking fifth nationally. Sixteen of 17 manufacturing industries rank within the top eight, with non-metallic mineral products, textiles, and electrical machinery leading. Longitudinal analysis reveals bifurcated development: steady growth (2011-2016) followed by volatility (2016-2020), with significant decline during COVID-19. Henan demonstrates robust servitization capacity with comprehensive multi-sectoral development, though external vulnerabilities persist during economic shocks and policy transitions. Strategic recommendations include establishing provincial servitization funds, building digital service platforms, strengthening talent development systems, implementing tax incentives for high-service enterprises, and creating monitoring frameworks to enhance policy effectiveness and industrial competitiveness.